1999
DOI: 10.1089/088922299309991
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor beta Is a Growth-Inhibitory Cytokine of B Cell Lymphoma in SIV-Infected Macaques

Abstract: Cytokine dysregulation is accepted as one of the pivotal factors in the pathogenesis of B cell lymphomas in HIV-positive patients. So far no data exist on inhibitory cytokines in the regulatory network of HIV-associated B-NHL. Simian immunodeficiency virus (SIV)-infected macaques are a well-established in vivo model of HIV infection in humans. We used this model for the identification of TGF-beta as a growth-inhibitory cytokine of SIV-associated B cell lymphomas. Fifty-seven rhesus macaques were infected with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…Using an immunoblastic SAIDS-NHL cell line shown to represent the original tumor mass (Figure 1), initial studies confirmed a previous report [20] that SAIDS-NHL cells may be sensitive to TGF-β1-mediated growth inhibition in a dose-dependent manner (Figure 2A). The marked sensitivity to growth inhibition by TGF-β1 suggested that a counteracting positive influence may be operative in SAIDS-NHL.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…Using an immunoblastic SAIDS-NHL cell line shown to represent the original tumor mass (Figure 1), initial studies confirmed a previous report [20] that SAIDS-NHL cells may be sensitive to TGF-β1-mediated growth inhibition in a dose-dependent manner (Figure 2A). The marked sensitivity to growth inhibition by TGF-β1 suggested that a counteracting positive influence may be operative in SAIDS-NHL.…”
Section: Resultssupporting
confidence: 79%
“…Based on the previous report of sensitivity of a single SAIDS-NHL-derived cell line to TGF-β1-mediated inhibition [20], an investigation was initiated to determine whether the finding could be recapitulated in LCL8664, a SAIDS-NHL-derived cell line from the Tulane National Primate Research Center characterized morphologically as immunoblastoid DLBCL [8]. LCL8664, like the original tumor, is of B-cell origin and is infected with rhesus lymphocryptovirus (RhLCV), the rhesus homologue of human EBV [7,9].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…where f ∶ R n+1 → R n is analytic for ∈ R, x ∈ R n . Let x = x 0 ( ) be a class of equilibrium points of Equation 13, ie, f(x 0 ( ), ) = 0. We now set y = x − x 0 ( ),…”
Section: Bifurcation Analysismentioning
confidence: 99%
“…8,9,12 Regarding the functions of the cytokines expressed in patients with NHL, TGF-acts as a negative growth regulator of the lymphoma-derived cell line and has been shown to be potentially an inhibitory factor in the regulatory network of AIDS-related lymphomagenesis. 4,13 It has an immunosuppressive role, mediated predominantly by its effects on T cells and antigen-presenting cells, 14 thus favoring the growth of malignancies. As indicated by Kekow et al, 15 TGF-is likely to contribute to the deficit in T cell surveillance, which is of paramount importance in suppressing tumor growth.…”
mentioning
confidence: 99%